Modifikasi Alat Ukur Fear of Online Identity Theft (FOIT) pada Transaksi Online di Indonesia - Raudyatuh Zahra Latief (Asosiasi Psikologi Forensik (Apsifor), 2026)
One of the phenomena associated with problems in online activities is the increasing prevalence of data breaches across various online platforms. Therefore, this study aims to develop a measurement instrument for fear of identity theft in the context of online transactions. This study modified the Fear of Online Identity Theft (FOIT) scale, which consists of two dimensions: Fear of Financial Losses (FFL) and Fear of Reputational Damage (FRD). Confirmatory Factor Analysis (CFA) and reliability analysis were conducted to evaluate the developed instrument. Additional analyses, including independent sample difference tests and linear regression, were also performed to provide a broader understanding of FOIT and its influencing factors. The findings indicate that the FOIT scale demonstrates excellent psychometric properties, with a Cronbach’s alpha coefficient above 0.90, indicating high reliability. The developed scale consists of 11 final items, which showed a better model fit compared to the initial 20-item model. The pilot-tested scale was proven capable of measuring fear of online identity theft among social media users. Further analyses revealed that gender moderated the relationship between the frequency of mobile banking (m-banking) usage and FOIT. Specifically, among males, the relationship between m-banking usage frequency and FOIT was negative, whereas among females, the relationship was positive.